2015
DOI: 10.1103/physrevlett.114.100403
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Entanglement and its Application to Generating Cat States

Abstract: The Einstein-Podolsky-Rosen (EPR) paradox, which was formulated to argue for the incompleteness of quantum mechanics, has since metamorphosed into a resource for quantum information. The EPR entanglement describes the strength of linear correlations between two objects in terms of a pair of conjugate observables in relation to the Heisenberg uncertainty limit. We propose that entanglement can be extended to include nonlinear correlations. We examine two driven harmonic oscillators that are coupled via third-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Two-state oscillation of the BEC has been experimentally observed [26]. We present in Figure 6 predictions for this type of oscillation with N = 20 and n L = 2 where the solutions indicate states (38) with a separation of n = 16 atoms. The question becomes how to certify the quantum coherence of the embedded cat-states (38) that may be generated in the experiment where such oscillation is observed.…”
Section: Creation Of N-scopic Quantum Superpositionsmentioning
confidence: 82%
See 1 more Smart Citation
“…Two-state oscillation of the BEC has been experimentally observed [26]. We present in Figure 6 predictions for this type of oscillation with N = 20 and n L = 2 where the solutions indicate states (38) with a separation of n = 16 atoms. The question becomes how to certify the quantum coherence of the embedded cat-states (38) that may be generated in the experiment where such oscillation is observed.…”
Section: Creation Of N-scopic Quantum Superpositionsmentioning
confidence: 82%
“…In a separate paper, we examine a third criterion based on uncertainty relations and Einstein-Podolsky-Rosen steering [31]. Previous studies have proposed signatures (criteria or measures) for mesoscopic "cat" states (see for instance [3,4,22,25,[29][30][31][32][33][34][35][36][37][38][39]). These include proposals based on interference fringes, entanglement measures, uncertainty relations, negative Wigner functions and state fidelity.…”
Section: Introductionmentioning
confidence: 99%
“…In a fully degenerate configuration, the Wigner function of the TPS exhibits negativities [30,32,33], a clear signature of SG statistics, which is impossible to achieve by second-order down-conversion (SODC) and linear optics. Nonlinear steering has been proposed and verified based on a partially degenerate configuration [34]. González et al revealed the relationship between Gaussian entanglement and both number of seeded modes and intensity in the nondegenerate case [35].…”
Section: Introductionmentioning
confidence: 99%
“…The superposition state (1.1) giving rise to this paradox has motivated much research. This includes experiments that realize different forms of cat states [3][4][5][6][7][8][9][10][11], proposals to generate and detect cat states [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], alternative interpretations of quantum mechanics and of the cat state [29][30][31][32][33][34][35][36][37], and theories that modify quantum mechanics [38,39]. In this paper, we present criteria for mesoscopic quantum coherence (MQC) and mesoscopic quantum entanglement (MQE).…”
Section: Introductionmentioning
confidence: 99%